A comparison studies on financial implication in managing residential property (in-house vs. outsourcing) / Nur Atiqah Ab Rahman - Ab Rahman, Nur Atiqah (2010)
High rise buildings is really needed nowadays since the population of the Malaysian citizens are growing faster and this kind of building is the best solution to reduce the people's density. In Malaysia, peoples who have right on the high-rise unit parcel of the building can decide to run the building by either in-house or outsources their management. On deciding the management implementation, the most factors to be consider is financial. This is the crucial agenda faced by management team because they have to collect monthly management fund to run maintenance of the common property. This study focused on to identify the different on budget between in-house and outsource management; to describe and analyzed the factor that related to the choice of management practice; to investigate the link between financial budget and user satisfaction on managing residential property. In order to achieve the objectives identified, literature review was done; the data was collected by using interview and questionnaires. Either in-house or outsource management, they are using different resources, budget allocation and expenses which will influence quality of work and level of satisfaction which can be analyzed by analyzing level of occupant's satisfaction. The main findings reveal that the financial resources have a giving impact to the level of occupant's satisfaction. In simple words if management has enough money in-hand, the maintenance aspects will run well, or vice versa.